The prince and the princess : a Bohemian fairy tale - Mayer, Marianna; Rogers, Jacqueline (New York : Bantam Books, 1989)
A retelling of the Bohemian fairy tale about the prince who frees a lovely princess from the powers of a wicked wizard with the help of three talented companions.
"A Bantam Skylark book."
Booklist
School Library Journal
3-6
Keywords: Fairy tales; Folklore -- Czechoslovakia; Fairy tales; Folklore -- Czechoslovakia